Peri‐procedural Anticoagulation in Patients with Head and Neck Versus Extremity Venous Malformations. (10th October 2020) - Dharmarajan, Harish; McCoy, Jennifer L.; Jabbour, Noel; McCormick, Andrew; Xavier, Frederico; Correa, Debra; Padia, Reema
Abstract : Objective: (1) Review a multidisciplinary vascular anomalies center's practice regarding periprocedural anticoagulation for venous malformations (VM) and the associated risk of thromboembolic and disseminated intravascular coagulation (DIC) events. (2) Compare the risk of thromboembolic events and DIC post‐procedure between head and neck (H&N) and extremity VM patients. Methods: An Institutional Review Board (IRB)‐approved, retrospective chart review was performed on 120 VM patients. A thromboembolic event was defined as a thrombus formation post‐sclerotherapy or post‐surgery within 2 months in a distant or local venous structure not directly addressed by the procedure. Results: There were 39 cases involving the H&N and 81 cases based at the extremities. There were eight cases of post‐procedure thrombus formation within the extremity VM group (8/71; 11.3%) as opposed to 0 cases in the H&N group (OR: 0, 95% CI .00–.09), p = .049. There was no difference in incidence of post‐procedure thromboembolic events between those with elevated D‐dimer (H&N: 0%, extremity: 22.7%, 5/22) and normal D‐dimer values (H&N: 0%, extremity: 6.3% [1/16], P = .370). There was no difference in incidence of post‐procedure thromboembolic events between those who received periprocedural anticoagulation (H&N: 0%, extremity: 21%, 4/19) and those who did not (H&N: 0%, extremity: 8.2%, 4/49), (Extremity: OR: 3.00, .67–13.50, P = .206). Conclusion: Post‐procedure thromboembolism is rare in the treatment of venous malformations, especially in the head and neck subsite. Regardless of anticoagulation use, there were no thromboembolic events for H&N VM patients. Such events are rare, and the odds may approach zero, especially with small sample size. Level of Evidence: 4 Laryngoscope, 131:1163–1167, 2021